Examining Customer Value in Making Repeat Purchases Online Travel Agent Pegipegi - Firdha Apsyari; Ahyar Yuniawan (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of hedonic values, social values on customer satisfaction and their impact on customer loyalty online travel agents Pegipegi. This study uses four variables, namely hedonic value, social value, customer satisfaction and customer loyalty. The population used in this study were all customers of Pegipegi's online travel agent in Indonesia, involving 134 respondents who were selected by purposive sampling with non-probability sampling technique. This study uses structural equation modeling (SEM) with the AMOS program. The results of this study indicate that hedonic values and social values have a positive and significant influence on customer satisfaction. Meanwhile, customer satisfaction has a positive and insignificant effect on customer loyalty.